Contribution of Ramachandra Pandita to sanskrit literature. - Wadekar, M L.,Ed (Bharatiya Kala Prakashan, 2006)
Compilation of works chiefly on Hindu philosophy, Hindu prayers and commentaries on Vedic texts.